Método de avaliação de qualidade de serviço em sistemas multimídia utilizando um sistema genético nebuloso baseado em regras - Bertoni, Fabiana Cristina (2005)
The Quality of Service (QoS) available in the network is the most important parameter for the guarantee of the success in a multimedia transmission [Dressler 2003a]. In the current context of multimedia systems, handle systems to QoS control are essential to the applications have the desired quality in the service accomplishment. The human user of a multimedia application is the initial point of all the considerations regarding QoS, having this that worry about the perceivable effect to this user. Usually, users are not aware on how to specify low-level parameters, such bandwidth, not even to understand numerical values related to measurements of these. Thus, it is necessary that the system provides an abstraction level, so that the user can understand which is the quality of service which the network can offer in a certain instant. Then, the user can decide if he will place the application in execution or not. This work presents a new method to express the Quality of Service (QoS) in a multimedia connection. This method uses discrete values of QoS parameters, establishing a relationship among them through the use of a Fuzzy Genetic Rule-Based System (FGRBS) to obtain a single value that expresses the QoS of the connection. This final value is classified within a predefined QoS specification standard consisting of three sets: Optimal, Acceptable and Unacceptable, resulting in a definition of the Quality of Service in a user-level language.